The value of Chlortetracycline (Aureomycin) and Sulfamethazine fed independently and in combination to weanling beef calves following shipment - C.L. Drake; L.I. Smart; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1968)
Two hundred weaning calves were received in two shipments and placed on experiment. The calves were weighed, ear tagged and tattooed as rapidly as possible after being received, and were treated as follows: Treatment A - No oral medication (Control) Treatment B - Fed 350 mg. sulfamethazinel per head daily Treatment C - Fed 350 mg. chlortetracycline per head daily Treatment D - Fed 350 mg. sulfamethazine and 350 mg. chlortetracycline per head daily The cattle were fed sorghum silage to consumption and 3 lbs. sorghum grain (containing the medication) per head daily. They were injected with 10cc Combiotic (penicillin and streptomycin) when fever or respiratory difficulty occurred. Two replications of 100 calves each were used for this trial.
Keywords: Cattlemen' s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Chlortetracycline (Aureomycin); Sulfamethazine; Weaning